Existence of Positive Solution for Boundary Value Problems - Hussein, S. M . (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
This paper studies the existence of  positive solutions for the following boundary value problem :-   y(b) 0 Î± y(a) - Î² y(a) 0     bta             f(y) g(t) Î»y ï€½ ï€½ï‚¢ ï€¼ï€¼ï€½ï‚¢ ï‚¢ï€  The solution procedure follows using the Fixed point theorem and obtains that this problem has at least one positive solution .Also,it determines ( ï¬ ) Eigenvalue which would be needed to find the positive solution .